Ta có:\(\frac{x}{a}=\frac{y}{b}=\frac{z}{c}=\frac{x+y+z}{a+b+c}\)
Ta có:\(\frac{x}{a}=\frac{y}{b}=\frac{z}{c}=\frac{xa^2}{a^3}=\frac{yb^2}{b^3}=\frac{zc^2}{c^3}=\frac{a^2x+b^2y+c^2z}{a^3+b^3+c^3}\)
Ta có\(\frac{x}{a}=\frac{y}{b}=\frac{z}{c}\Rightarrow\frac{x^2}{a^2}=\frac{y^2}{b^2}=\frac{z^2}{c^2}=\frac{x^3}{a^2x}=\frac{y^3}{b^2y}=\frac{z^3}{c^2z}=\frac{x^3+y^3+z^3}{a^2x+b^2y+c^2z}\)
\(A=\frac{\left(x^3+y^3+z^3\right)\left(a^3+b^3+c^3\right)\left(a+b+c\right)}{\left(x+y+z\right)\left(a^2x+b^2y+c^2z\right)^2}=\frac{x^3+y^3+z^3}{a^2x+b^2y+c^2z}\cdot\frac{a^3+b^3+c^3}{a^2x+b^2y+c^2z}\cdot\frac{a+b+c}{x+y+z}\)
\(=\frac{x^2}{a^2}\cdot\frac{a}{x}\cdot\frac{a}{x}\)=1
[0ferh0g-y\pj=up-l][ki;,'j;.gk9r8goyu-[jl;mjfiweyu